Efisiensi Bank Umum dengan Pendekatan Data Envelopment Analysis (DEA) untuk Mewujudkan Green Banking di Indonesia - fitri, Heti Suryani Fitri; Abrianto, Heri; Ramadhani, Annisa Alifa; Dewanti, Lintang Kresna; Jatiningrum, Pebriantika Wahyu; Khairunnisa, Khairunnisa (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Banking competitiveness can be reflected in the level of operational efficiency. Measuring performance based on efficiency is very crucial for banks. Banks that have better performance must manage efficiency levels to be better able to compete. This research aims to determine the level of efficiency of commercial banks and the potential for improving commercial bank inefficiencies. This type of research is quantitative descriptive research. The sample taken used purposive sampling, namely taking KBMI 4 banks, namely commercial banks which have core capital of more than 70 trillion, consisting of Bank BNI, Bank Mandiri, Bank BCA and Bank BRI. The data analysis method uses Data Envelopment Analysis (DEA) and the software used is MaxDEA. The results of this research show that the KBMI 4 bank that has achieved the most perfect efficiency levels, namely an efficiency score equal to 1, is BRI. The reason for Bank KBMI's inefficiency 4 is that most of the resources used have not been able to increase interest income and fee based income. Potential improvements that can be made are by increasing Third Party Funds, increasing total assets, reducing labor costs and switching manual transaction strategies to digital transactions